Navigating Planning Crises: Karachi’s Response to COVID-19 (Journal of Asian Development Studies, 2024)
The COVID-19 pandemic has invariably highlighted the critical role of spatial planning in managing public health emergencies, particularly with the need for social distancing. Historically, effective spatial planning has been essential for governments in navigating crises such as floods and earthquakes, employing strategies like designating containment zones, repurposing infrastructure, and constructing temporary facilities. The research focuses on Karachi’s response to the pandemic. It examines how the city’s spatial planning strategies were adapted to meet the challenges of its dense urban environment and socio-economic diversity. As Pakistan’s largest city and economic hub, Karachi confronted significant challenges in balancing public health measures with financial activities. The study investigates how state institutions implemented awareness campaigns and emergency spatial planning, including the creation of quarantine centers, isolation zones, inoculation centers, and modifications to public spaces. Similar to other mega-cities, Karachi is vulnerable to natural disasters and emergencies, as it balances a range of issues that require effective spatial and urban planning. The city’s response to COVID-19 reflects broader trends in emergency planning, highlighting its approach to managing crises through strategic interventions. The study aims to uncover the complex relationship between spatial planning and crisis management by illustrating response timelines, temporary structures taxonomy, and infographics. It offers insights into how cities can better prepare for and respond to future crises. It emphasizes the importance of restructuring governance and adaptive and context-specific planning in urban health management.